Preoperative left atrial minimum volume as a surrogate marker of postoperative symptoms in senile patients with aortic stenosis who underwent surgical aortic valve replacement. Issue 4 (October 2019) - Morimoto, Junko; Hozumi, Takeshi; Takemoto, Kazushi; Wada, Teruaki; Maniwa, Naoki; Kashiwagi, Manabu; Shimamura, Kunihiro; Shiono, Yasutsugu; Kuroi, Akio; Yamano, Takashi; Yamaguchi, Tomoyuki; Matsuo, Yoshiki; et al.
Highlights: Symptoms are not rare after aortic valve replacement due to aortic stenosis. Preoperative left atrial volume was greater in postoperative symptom group. Left atrial volume can be a surrogate marker of postoperative symptom. Abstract: Background: Previous reports have shown that postoperative symptoms despite successful surgical aortic valve replacement (AVR) are not uncommon depending on severity of myocardial fibrosis in patients with aortic stenosis (AS). Left atrial minimum volume (LAVmin ) at end-diastole determined by direct exposure of left ventricular end-diastolic pressure may be useful as a surrogate marker of postoperative symptoms in patients with AS undergoing AVR. Methods and results: We studied 75 patients with AS who underwent AVR and were followed up to 600 days after AVR. We examined the postoperative symptomatic status which occurred between 60 days to 600 days after AVR. The study patients were divided into 2 groups: 19 patients (25%) with postoperative symptoms (symptomatic group) and 56 without symptoms (asymptomatic group). There were no significant differences in preoperative left ventricular volumes and ejection fraction and AS severity by echocardiography between the two groups. There were significant differences in preoperative echocardiographic LAVmin index (LAVImin ) between symptomatic group and asymptomatic group (45 ± 15 vs. 28 ± 11 ml/m 2 ). Using receiver operating characteristic curve analysis, LAVImin ≥ 30 ml/m 2 detected postoperative symptoms with the large area under the curve (0.84) (sensitivity 94% and specificity 68%). In the multivariate analysis, preoperative LAVImin was the independent predictor of the postoperative symptomatic status after AVR (odds ratio: 1.11; 95% CI: 1.04–1.18). Conclusions: The preoperative echocardiographic LAVImin measurement is useful as a surrogate marker of symptomatic status after AVR in patients with AS.